Clinical Pharmacogenetics Implementation Consortium (CPIC) Guidelines for Rasburicase Therapy in the Context of G6PD Deficiency Genotype. Issue 2 (2nd May 2014) - Relling, M V; McDonagh, E M; Chang, T; Caudle, K E; McLeod, H L; Haidar, C E; Klein, T; Luzzatto, L
<x xml:space="preserve">Abstract</x> Glucose‐6‐phosphate dehydrogenase (G6PD) deficiency is associated with development of acute hemolytic anemia (AHA) induced by a number of drugs. We provide guidance as to which G6PD genotypes are associated with G6PD deficiency in males and females. Rasburicase is contraindicated in G6PD‐deficient patients due to the risk of AHA and possibly methemoglobinemia. Unless preemptive genotyping has established a positive diagnosis of G6PD deficiency, quantitative enzyme assay remains the mainstay of screening prior to rasburicase use. The purpose of this article is to help interpret the results of clinical G6PD genotype tests so that they can guide the use of rasburicase. Detailed guidelines on other aspects of the use of rasburicase, including analyses of cost‐effectiveness, are beyond the scope of this document. Clinical Pharmacogenetics Implementation Consortium (CPIC) guidelines are published and updated periodically on https://www.pharmgkb.org/page/cpic to reflect new developments in the field. Clinical Pharmacology & Therapeutics (2014); 96 2, 169–174. doi:10.1038/clpt.2014.97